Power Consumption Optimization in CNC Turning Process Using Multi Objective Genetic Algorithm - Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas; Riza, Muhammad; Suprianto, Mohamad Yuhan (Trans Tech Publications, Switzerland, 2012)
Power consumption cost is one of the main integral parts of the total machining cost, but it has not given the proper attention when minimizing the machining cost. In this paper, the optimal machining parameters for continuous machining are determined with respect to the minimum power consumption cost with maintaining the surface roughness in the range of acceptance. The constraints considered in this research are cutting speed, feed rate, depth of cut and rake angle. Due to complexity of this machining optimization problem, a multi objective genetic algorithm (MOGA)was applied to resolve the problem, and the results have been analyzed.